2020
DOI: 10.1111/pbi.13464
|View full text |Cite
|
Sign up to set email alerts
|

The miR156/SPL module regulates apple salt stress tolerance by activating MdWRKY100 expression

Abstract: Summary Salt stress dramatically impedes plant growth and development as well as crop yield. The apple production regions are reduced every year, because of the secondary salt damage by improper fertilization and irrigation. To expand the cultivation area of apple (Malus domestica) and select salt‐resistant varieties, the mechanism of salt tolerance in apple is necessary to be clarified. The miR156/SPL regulatory module plays key roles in embryogenesis, morphogenesis, life cycle stage transformation, flower fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(77 citation statements)
references
References 56 publications
1
70
0
Order By: Relevance
“…These observations indicated that a subset of VcSBP s might be involved in the regulation of chlorophyll accumulation. Previous studies have revealed that SBP family proteins can directly interact with their clients (for example, AtFUL , AtSOC1 , AtDFR , AtAP1 , MdWRKY100 , MaLCYB1.1 , and MaLCYB1.2 , MADS5 , and MADS32 ), thereby regulating diverse biological processes in plants such as flowering, inflorescence formation, biosynthesis of secondary metabolites, root regeneration, and response to stress ( Yamaguchi et al, 2009 ; Gou et al, 2019 ; Ma et al, 2020 ; Zhu et al, 2020 ). However, the targets of SBP proteins associated with chlorophyll accumulation have remained to be found.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicated that a subset of VcSBP s might be involved in the regulation of chlorophyll accumulation. Previous studies have revealed that SBP family proteins can directly interact with their clients (for example, AtFUL , AtSOC1 , AtDFR , AtAP1 , MdWRKY100 , MaLCYB1.1 , and MaLCYB1.2 , MADS5 , and MADS32 ), thereby regulating diverse biological processes in plants such as flowering, inflorescence formation, biosynthesis of secondary metabolites, root regeneration, and response to stress ( Yamaguchi et al, 2009 ; Gou et al, 2019 ; Ma et al, 2020 ; Zhu et al, 2020 ). However, the targets of SBP proteins associated with chlorophyll accumulation have remained to be found.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the MsWRKY11 gene enhanced salt tolerance in soybean by increasing soluble protein and proline contents and reducing ROS levels, but the detailed regulatory mechanisms remain to be further investigated . MdWRKY100 overexpression enhanced salt tolerance in M. domestica, which was upregulated by the miR156/SPL regulatory module (Ma et al, 2021). MxWRKY64, which is a new WRKY transcription factor gene from Malus xiaojinensis, was induced to express by salt stress in M. xiaojinensis seedlings.…”
Section: Induction Of Transcription Factor Expressionmentioning
confidence: 98%
“…The IbWRKY47 gene positively regulates stress resistance-related genes and significantly improves the salt tolerance of Ipomoea batatas [68]. MiR156/SPL modulates salt tolerance by upregulation of Malus domestica salt tolerance gene MdWRKY100 [71]. In Sorghum bicolor, SbWRKY50 could directly bind to the upstream promoter of SOS1 and HKT1 and participate in plant salt response by controlling ion homeostasis [67].…”
Section: Wrky Tfs and Salt Stressmentioning
confidence: 99%